Professionals' perceptions of electronic and online sexual behaviors of youth in their community. (April 2020) - Taylor, Erin K.; Slemaker, Alexandra; Silovsky, Jane F.
Highlights: US professionals reported on perceptions of electronic sexual behavior of youth. Electronic sexual behavior is perceived to be frequent, increasing, and concerning. The most behaviors were sexting and viewing online pornography. Caregivers reportedly struggle with supervision and monitoring of these behaviors. Professionals lack clear policies and procedures for addressing these behaviors. Abstract: Over the past decade, internet access has become deeply ingrained in the daily lives of individuals across the world, with particularly rapid growth in its use by children and adolescents. In the United States (U.S.), 45% of teens report using the internet "almost constantly" (p. 8; Anderson et al., 2018). With such increased availability of technology, concerns have arisen regarding how easily youth can engage in sexual behaviors online or via electronics, like viewing pornography or "sexting." Despite this increase in concern, many professions responsible for youth (e.g., schools, law enforcement, child welfare) are faced with navigating and guiding youth online behavior. However, limited research to date has examined how professionals who work with youth, specifically those who have engaged in other problematic sexual behavior, perceive and conceptualize electronic and online sexual behavior. We conducted qualitative interviews with 36 professionals from different disciplines across eight sites. Participants were asked about their perceptions of youth use of technology; changes in rates of electronic and online sexual behaviors over time; the severity, frequency, and impact of the behavior; and typical community responses to the behavior. Stakeholders perceived youth's engagement in electronic and online sexual behaviors to be frequent, growing, and concerning yet reported that they lacked clear protocols to determine the severity of these behaviors and guide responses. Implications of the results for prevention efforts, future research directions, and policy development are discussed.